Distinctive morphometric measurement of frontal sinuses among the female ethnic populations living in Karachi - Quratulain Javaid; Ambreen Usmani (Journal of the Pakistan Medical Association, 2021)
Abstract Objective: To determine uniqueness of frontal air sinuses in the female ethnic populations living in Karachi Methods: The study type was cross sectional descriptive study. It was conducted at the Radiology Department of Jinnah Postgraduate Medical Center from November 2018 to April 2019. The research participants were females and 108 in number. They were divided into four ethnic groups. Each ethnic group consisted of 27 members. Mean age of the research participants was 35.14 ± 8.68 years. Before the enrolment of the participants in the research, informed consent was taken. Frontal sinus, X-ray radiography was done by using STEPHNEX machine. The radiological view incorporated was Water’s view. Width, height and area of the right and left frontal sinuses were measured. The radiographs were saved in the JPEG format and then the measurements were done by RadiAnt DICOM digital software. In the proforma measurements of height, width and area were noted. Data analysis was done by using the SPSS version 23.0. Results: Comparison of the ethnic groups was done by using the application of One Way ANOVA. When the parameters of the frontal air sinuses were compared, variability in terms of width, height and area were noted in the right frontal air sinuses (p=0.000). Highly significant variations were also noted for these parameters on the left side (p=0.000). Conclusion: The width, height and area of right and left frontal sinuses showed variability among the female ethnic groups living in Karachi. Continuous...